Broadening Relevance: The Polemic Property of Concepts in Metaphorical Language - Salim Bouherar; Ramona Pistol (European Scientific Journal, ESJ, 2020)
The lexical pragmatic processes that relevance theory heavily relies on to account for communication are problematic. Broadening and narrowing no longer seem suitable to explain how “conceptual” meanings are modified in the comprehension processes if considering recent developments around the concept definitions and how the mind works. Using theoretical suggestions in psycholinguistics to shed light on the issue raised, the paper makes two main suggestions. Firstly, the account of concepts in relevance theory should be reconsidered to allow for more flexibility. An account of metaphors based on pragmatic adjustment of one of its constituents under the influence of another, as well as contextual assumption, does not seem a viable mental process involved in metaphor comprehension since it should not only allow flexibility of semantic associations but also a reconsideration of concepts as entities and encyclopaedical information as mere conceptual characteristics. Secondly, more cultural awareness and influence should be integrated into the relevance theoretical account of meaning since cultural traits are often considered by speakers in reaching relevance. Moreover, pre-existing conceptual knowledge varies greatly between individuals and thus the comprehension of metaphor should no longer be treated as a static process but rather a highly dynamic one.